Reflective Journal Implementation as a Form of Professionalism of Prospective Basic Education Teachers - Nasyariah Siregar; Fia Alifah Putri; Vioni Saputri (Universitas Muhammadiyah Enrekang, 2023)
Reflective journal writing is an underdeveloped platform in the professional teacher environment. Tanoto Foundation's efforts to become reflective practitioners, institutions must encourage professional teachers to use reflective journals as a way of evaluating and monitoring their teaching practice, so that teachers are more effective in the context of direct teaching in the 21st century era. With the aim of research on how to implement reflective journals, efforts to implement reflective journals, and obstacles in implementing reflective journals as a form of MI teacher professionalism. This research method uses a descriptive qualitative method with a population of PGMI students in semester VII of the 2022/2023 academic year, totaling 210 practicing students spread throughout the city and several Jambi districts. The sample used is a non-probability sample using a purposive sampling technique that uses a sample of students who teach in high grades, namely grades 4, 5 and 6, with 3 practicing students. The results of this study were that there was an increase from the first meeting in teaching and learning activities after implementing reflective journals, as seen from the second meeting. With observations at the first meeting before implementing reflective journals as a form of teacher professionalism it has a total score of 75% which is in the